Religion and tradition in conflict: Experimentally testing the power of social norms to invalidate religious law - Christoph Engel; Klaus Heine; Shaheen Naseer (Max Planck Institute for Research on Collective Goods, 2021)
Often, religion, law and tradition co-evolve. Religious precepts shape social practice, which translates into law. Yet this harmony is not universal. The Sharia guarantees daughters their share in the family estate. Yet in Pakistan, this rule clashes with tradition. While the country was jointly governed with (mainly Hindu) India, it had been customary that the entire estate goes to the eldest son. Combining a survey with a lab in the field experiment, we show that this is still the descriptive and the injunctive norm. Yet participants have a strong preference for the conflict to be dissolved by legislative intervention.
hdl:21.11116/0000-0008-9A79-3
Keywords: C91; C93; D01; D15; D31; D63; J16; K00; O12; O53; R22; 330; religious norm; legal rule; descriptive and injunctive social norm; inheritance; gender discrimination; Sharia; experiment